ANALISIS NILAI TAMBAH RUMPUT LAUT SEBAGAI PRODUK PANGAN PADA KELOMPOK USAHA “ARES” KOTA MATARAM - IDA BAGUS EKA ARTIKA; IDA AYU KETUT MARINI; A. A. MADE SURYA KENCANA; IDA AYU NOPIARI; INDAH ARIFFIANTI (Universitas Mahasaraswati K. Mataram, 2021)
Processing raw materials into a product with higher value added is a positive endeavor, to provide higher benefits for the welfare of society. Seaweed as one of the mainstay commodities in the West Nusa Tenggara region will provide high benefits if it is successfully processed into products with a higher selling value than if it is sold as a ra product. This study aims to determine the value added of processed food products made from seaweed, namely seaweed rengginang, seaweed kripik and seaweed crackers which are processed by the